Sharecropping, migration and the new face of water markets: a case of Sangpura Village in North Gujarat - Prakash, Anjal (International Water Management Institute, 2005)
Research highlight based on a PhD thesis titled "The dark zone: Groundwater irrigation, politics and social power in North Gujarat."